Derrière l’écran, les négociations collectives dans le cinéma (1975-2020) - Samuel Zarka (La Nouvelle Revue du Travail)
The professional branch has been the predominant normative space in the film and audiovisual industries since the 1990s. This observation contrasts with the recent reforms of labour law, which make the company the central body for the formulation of law, in order to adapt it continuously to the fluctuating demand. This paradox leads us to question the function of legal benchmarks set at the branch level in a project-based industry. To this end, we look back at the way in which actors in industrial relations have invested this level of collective bargaining in recent decades, the framing of the activity that has resulted from it and the reasons for its stability in the course of contemporary productive recompositions.